Sandpile Models in the Large - Ruelle, Philippe (Frontiers in Physics, 2021)
This contribution is a review of the deep and powerful connection between the large scale properties of critical systems and their description in terms of a field theory. Although largely applicable to many other models, the details of this connection are illustrated in the class of two-dimensional Abelian sandpile models. Bulk and boundary height variables, spanning tree related observables, boundary conditions and dissipation are all discussed in this context and found to have a proper match in the field theoretic description.